Learnt And Perceived Professional Role: A Focus Group Discussion of Tourism Students’ Internship In A Hotel In Indonesia - Friska Ria Sitorus; Wolter Parlindungan Silalahi (Jayapangus Press, 2023)
The internship program provides students with a good experience developing their potential to prepare themselves to work in the future. This paper focuses on looking at students' experiences in carrying out internships in a hotel in rural areas far from the center of the crowd. This qualitative study aims to examine the experiences of undergraduate tourism students conducting an internship program which approximately three months to see the reality of world work at a hotel. The study was designed with a descriptive qualitative method to study the participants’ experiences. This study conducted the data through focus group discussions and a semi-structured interview. The data obtained were analyzed through transcribing, coding, managing, and interpreting. This study involved four undergraduate tourism students aged twenty-one to twenty-three years old. This study revealed the benefits and the challenges they got through the internship program at the hotel. The benefits include learning disciplines, self-development, and gaining new skills. The challenges include adaptation to the skills required in work, such as responsibility, teamwork, and communication, limited days off, and limited public transportation around the internship site. This study concluded that students learned various skills and knowledge at the internship site through guidance from the supervisor and team. As a result, they achieve self-development and skills useful for their career in the future.